Myxobolus cerebralis Causes Presporogonic Mortality in Juvenile Mountain Whitefish. Issue 2 (29th April 2021) - Americus, Benjamin; Schisler, George J.; Bartholomew, Jerri L.; Atkinson, Stephen D.
Abstract: Recent range expansions of whirling disease impelled us to understand the impacts of its causative agent, the myxozoan parasite Myxobolus cerebralis, on lesser‐studied fish hosts. Mountain Whitefish Prosopium williamsoni overlap broadly with M. cerebralis across the western United States and Canada, and populations have experienced widespread declines since the 1990s. To evaluate effects of the parasite on Mountain Whitefish, we revisit formerly unpublished work of the Colorado Division of Wildlife (now Colorado Parks and Wildlife), comparing infection in age‐matched Mountain Whitefish, Rainbow Trout Oncorhynchus mykiss, and Brown Trout Salmo trutta . To complement the original report, we reanalyze mortality data and include additional SEM imagery. Infection of M. cerebralis in juvenile Mountain Whitefish was characterized by a brief but heavy period of mortality in the first 2 weeks after exposure, with limited pathology. This clinical effect is unique among the known salmonid hosts of M. cerebralis .